P249 Informing the pathway of COPD treatment (the IMPACT study): single inhaler triple therapy (FF/UMEC/VI) versus dual bronchodilator therapy (UMEC/VI) in patients with COPD – cost-effectiveness in the UK. (December 2018) - Anley, G; Shah, D; Schroeder, M; Ndirangu, K; Risebrough, N; Okorogheye, G; Fenwick, E; Martin, A; Ismaila, AS
Abstract : Introduction and objective: Exacerbations associated with chronic obstructive pulmonary disease (COPD) are costly and affect health related quality of life (HRQoL) for patients. An economic model was developed to estimate the cost-effectiveness of once-daily single-inhaler triple-therapy, fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) Trelegy ®, 100 µg/62.5 µg/22 µg and dual therapy, umeclidinium/vilanterol (UMEC/VI) Anoro ®, 55 µg/22 µg from a UK NHS perspective using results from the IMPACT study (NCT02164513 ). Patients and methods: The model combines a decision tree for the within-trial period (52 weeks) and a Markov model to predict lifetime costs and outcomes of FF/UMEC/VI compared with UMEC/VI. Risk equations for prediction of exacerbations (by severity of COPD) and FEV1 decline (based on exacerbation history) were derived using data from the TORCH study (NCT00268216 ). Baseline characteristics, efficacy and medication use were based on data from IMPACT. Direct costs, including drug acquisition costs were calculated using UK NHS reference costs and drug prices. Healthcare resource utilisation was based on published sources. Costs (2018 £) and health outcomes were discounted at 3.5% and modelled on a lifetime horizon. Sensitivity analyses were performed to evaluate the robustness of the model to variations in the underlying input parameters and assumptions. Results: Patients treated with FF/UMEC/VI had fewer moderate and severe exacerbations, more life years gained, improved HRQoL and higher total costs compared with patients treated with UMEC/VI based on deterministic analyses (table 1). The incremental cost-effectiveness ratio (ICER) was £7451 per QALY gained. Sensitivity analyses identified that results were most sensitive to drug acquisition cost, utilities associated with moderate COPD and severe COPD, mortality risk in very severe COPD, and exacerbation rates. The ICERs ranged from £1110 to £13 793 per QALY. Probabilistic sensitivity analysis indicated a 73% chance that FF/UMEC/VI is cost-effective versus UMEC/VI at a willingness to pay threshold of £20 000 per QALY. Funding: GSK (study number HO-17–17596). ICON Health Economics received funding from GSK to conduct the study only.